Mister Pulitzer and the Spider : Modern News from Realism to the Digital - Barnhurst, Kevin G., 1951- (Book collections on Project MUSE., 2016)
A spidery network of mobile online media has supposedly changed people, places, time, and their meanings. A prime case is the news. Digital webs seem to have trapped 'legacy media', killing off newspapers and journalists' jobs. Did news businesses and careers fall prey to the digital 'spider'? To solve the mystery, Kevin Barnhurst spent 30 years studying news going back to the realism of the 1800s. The usual suspects - technology, business competition, and the pursuit of scoops - are only partly to blame for the fate of news.